Insights into the interplay among zinc, biological aging, fasting, energy intake, and inflammation: A cross-sectional analysis using 2015-2018 NHANES participants - Rebecca Lake; Juan Liuzzi; Changwon Yoo (Journal of Trace Elements and Minerals)
Introduction: Although it is documented that zinc plays an essential role in immune function, little is known about its relationship to factors that influence biological aging. The primary objective of this study is to investigate how fasting status, total energy intake, and carbohydrate intake interfaces with dietary zinc intake and acute inflammation status via HS-CRP in young adults. Materials and methods: A nationally representative sample of 1,211 adults (ages 19-35 years old) from the 2015-2018 National Health and Nutrition Examination Survey cycles was included in this cross-sectional analysis. The data derived from the first and secondary dietary recall, fasting questionnaire, physical examination, and bloodwork collected at the Mobile Examination Center. HS-CRP levels were associated with dietary zinc intake and either fasting status, energy intake, and or carbohydrate intake while adjusting for WBC count, choline intake, folate intake, BMI, and gender. Survey weighted generalized linear models were constructed and the Rao-Scott likelihood ratio test was implemented via the survey package in R. Results: A two-way interaction effect was identified between the variables Adequate Zinc Intake, defined as consuming at least 8 mg of zinc per day and Fasted defined as fasting for 9 or more hours, which was associated with a reduction in circulating HS-CRP (OR = 0.56, 95 % CI: 0.33-0.96, p = 0.038). Fasting was associated with higher levels of HS-CRP (OR = 1.76, 95 % CI: 1.12-2.76, p = 0.016). No other models were significant. Conclusion: Short-term fasting was associated with an increase in HS-CRP; however, adequate zinc intake during fasting may lower circulating levels of HS-CR.